A Thermofluid Analysis of the Magnetic Nanoparticles Enhanced Heating Effects in Tissues Embedded with Large Blood Vessel during Magnetic Fluid Hyperthermia. (18th April 2016) - Adhikary, Koustov; Banerjee, Moloy
Abstract : The thermal effect developed due to the heating of magnetic nanoparticles (MNPs) in presence of external magnetic field can be precisely controlled by the proper selection of magnetic absorption properties of the MNPs. The present paper deals with the numerical simulation of temperature field developed within or outside the tumor, in the presence of an external alternating magnetic field, using a thermofluidic model developed using ANSYS FLUENT®. A three-layer nonuniform tissue structure with one or two blood vessels surrounding the tumor is considered for the present simulation. The results obtained clearly suggest that the volumetric distribution pattern of MNPs within the tumor has a strong influence on the temperature field developed. The linear pattern of volumetric distribution has a strong effect over the two other types of distribution considered herein. Various other important factors like external magnetic field intensity, frequency, vascular congestion, types of MNP material, and so forth are considered to find the influence on the temperature within the tumor. Results show that proper selection of these parameters has a strong influence on the desired therapeutic temperature range and thus it is of utmost importance from the efficacy point of view of magnetic fluid hyperthermia (MFH).